Direk : essays on Filipino filmmakers - Del Mundo, Clodualdo, Jr., 1948-; Lua, Shirley O. (Sussex Academic Press, 2019)
Direk, a collection of essays on Filipino filmmakers, presents an accessible and provocative introduction to Philippine cinema. Notable Filipino critics write on the canonical Filipino film directors: Ronald Baytan on Ishmael Bernal; Patrick F Campos on Kidlat Tahimik; Clodualdo Del Mundo, Jr. on Manuel Silos, Eddie Romero, and Lamberto Avellana; Vicente Garcia Groyon on Peque Gallaga; Shirley O. Lua on Fernando Poe, Jr; Gil Quito on Marilou Diaz-Abaya and Lav Diaz; Anne Frances N Sangil on Mike de Leon; Agustin Sotto on Gerardo de Leon; Nicanor G Tiongson on Manuel Conde; Rolando B Tolentino on Lino Brocka; Noel Vera on Mario OHara; and Lito B Zulueta on Brillante Ma Mendoza. A compelling work, the first of its kind, it is filled with insight and critical provocation. The work is essential reading for all who are interested in film making in all its multiple aspects, and provides hitherto unavailable information on Philippine filmmakers and cinema.
Keywords: Motion pictures -- Philippines.; Motion pictures -- Production and direction -- Philippines.; Motion picture producers and directors -- Philippines.; Motion picture industry -- Philippines.; Cinéma -- Production et réalisation -- Philippines.; Producteurs et réalisateurs de cinéma -- Philippines.; Cinéma -- Industrie -- Philippines.; Cinéma -- Philippines.; PERFORMING ARTS -- Reference.; Motion pictures -- Production and direction; Motion picture producers and directors; Motion picture industry; Motion pictures; Philippines